Knowledge of Self Help Group Women Members Regarding Food Processing and Dairy Management Practices (Indian Journal of Extension Education, 2012)
The present study was conducted in Parbhani district of Marathwada region of Maharashtra state to study knowledge level of Self-Help Group (SHG) women and their profile. Parbhani and Gangakhed talukas of Parbhani district were purposively selected. A sample of 120 respondents was purposively selected, based on their involvement in food processing and dairy management, considering 60 respondents from each taluka. The respondents were interviewed with the help of well-structured interview schedule. The findings revealed that majority of the respondents had medium level of knowledge in food processing and dairy management practices.